Dieulafoy Lesion: Predictive Factors of Early Relapse and Long-Term Follow-Up - Massinha,Paulo (2020)
Introduction: The Dieulafoy lesion (DL) is a rare cause of gastrointestinal bleeding. Advances in the endoscopy field have allowed an increased rate of detection and therapeutic efficacy. However, doubts remain about the most effective hemostatic approach, the affecting variables of therapeutic failure, and early relapse, as well as in the long-term followup. Aims: To assess the efficacy of endoscopic treatment of DL and to identify possible risk factors for early relapse and long-term results. Methods: All patients with DL admitted to a tertiary hospital between 01/01/2007 and 12/31/2018 were evaluated. The form of presentation, associated pathologies, chronic medication, therapeutic approach, and eventual relapse were determined. A telephone interview was conducted for all patients to find out the long-term results. Results: We identified 73 patients with DL, 45 (61.6%) males, with a mean age of 74 ± 15 years. Thirty-nine patients presented the DL in the stomach, 15 in the duodenum, 2 in the small bowel, 3 in the colon, and 11 in the rectum. The median number of endoscopic examinations required for diagnosis was 2. Median Rockall was 4 (range 2-7). After endoscopic treatment, in 95% of the cases, no active bleeding was evident. Only 2 patients required interventional radiology procedures and 1 needed surgery. Fourteen patients (19%) had a rebleeding, 12 during hospitalization and 2 after a median time of 51 months (range 1-117). There was no difference between the groups with and without early relapse in relation to age, gender, hemoglobin values at presentation, presence of shock, associated pathologies, and anticoagulation. Antiplatelet agents intake had a statistically significant relationship with early relapse (p = 0.003). Conclusion: Endoscopic therapy is safe and effective in DL. Patients under antiplatelet therapy are more likely to have an early relapse. The long-term prognosis is excellent, even in patients only treated with endoscopic methods.